Heritage Languages Acquired, Learned, and Used among Kalimantan University Students, Indonesia: A Perception - Aries Utomo (JALL (Journal of Applied Linguistics and Literacy), 2023)
Heritage language is a language taught and learned from parents. It was integrated from generation to generation. In Kalimantan, heritage languages are very various and has developed due to many influences from internal and external factors. This research aims (1) to describe how students perceive the languages(s) they acquired, learned, and used and (2) to describe their use and perceptions on heritage languages maintenance. This research was a qualitative statistic. In collecting data, the researcher employed interview, questionnaire, and observation. In analyzing data, the researcher relied on Miles and Huberman model for qualitative data and statistic formulas for quantitative data. Based on the findings, it was found that (1) students perceive the languages they acquired, learned, and used in specific ways from the three languages mastered, such as involving in a language community, communicating with family members, friends, including learning from TV or film, and (2) students feel happy to use their HL to communicate with people with different backgrounds and show their identities. Therefore, it can be concluded that students acquire, learn, and use their languages into various ways, while maintaining those languages, they tend to involve in a language community and family members. Indeed, students from various ethnic backgrounds can make the learning process meaningful by knowing many local languages and cultures in a classroom.